Feeding behavior of the mealybug Phenacoccus herreni (Sternorrhyncha: Pseudococcidae) and influence of water deficiency in cassava plants on its development - POLANIA, MARIA ALEJANDRA; CALATAYUD, PAUL-ANDRE; BELLOTII, ANTHONY C. (Revista Colombiana de Entomología, 1999)
The cassava mealybug  Phenacoccus herreni Cox  &  William (Stemorrhyncha:  Pseudococcidae) is an important pesto of cassava, Manihot esculenta Crantz (Euphorbiaceae),  especially during drought, when insect populations increase. This phenomenon might be a response to biochemical changes in cassava leaves induced by water deficiency, which enhanced insect development. In order to verify this phenomenon, it was first necessary to study its feeding behaviour. Observation of the mouthparts by scanning electron microscopy was carried out and the feeding activity was studied by electronpenetrography (EPG). Insect biological development and reproductive rate, and also infected leaf amino acid composition from cassava plants grown with differential irrigation levels (well-watered and deficiently watered) were evaluated. The influence on P. herreni development of the amino acids that's increased their proportion in water-stressed plants was evaluated using artificial diet. The results showed that P. herreni in mainly a phloemophaegous insect with piercing-sucking mouthparts and they feed on phloem sap throughout their lives cycle, we suggest that the females are more responsible for cassava damage and therefore subsequent studies were done on females. Water stress in plants induced a reduction in the duration on females development and an increase in fecundity, intrinsic natural growth rate (rm) and in weight. Leaf amino acid composition showed a more important increase in the proportion of free asparagine. Using an artificial diet it was shown that this amino acid may play an important role during the development of P. herreni. In fact, its absence in the diet-induced an insect development delay.